Thermal Evolution of Pt-Rich FePt/Fe3O4 Heterodimers Studied Using X-ray Absorption Near-Edge Spectroscopy - Figueroa, S. J. A. (2011)
FePt/Fe3O4 nanoparticles can be used as building blocks to obtain, upon thermal annealing, magnetic nanocomposites with combined magnetic properties. Although the pre- and postannealed samples are usually well-characterized, a detailed investigation during annealing is necessary to reveal the role of intermediate processes to produce a desirable composite. We present an alternative method using in situ XANES to investigate the thermal evolution of oleic acid- and oleylaminecoated Pt-rich FePt/Fe3O4 heterodimers. As the temperature increases, a progressive reduction of Fe3O4 to FeO occurs helped by the thermolysis of the surfactants, while above 550 K Fe3Pt starts to be formed. At 840 K an abrupt increase of FeO further drives the phase transformation to stabilize the iron platinum soft phase. Thus, the Fe3O4 reduction acts as catalyst that promotes the Fe and Pt interdiffusion between the Pt-rich FePt and Fe3O4/FeO to form Fe3Pt instead of exchange-coupled FePt/Fe3O4 with hard magnetic properties. In addition, the role of the interface of the heterodimer ends is discussed. The pre- and postannealed samples were also characterized by TEM, XRD, EXAFS, magnetometry, and Mössbauer spectroscopy.